Significant and serious dehydration does not affect skeletal muscle cramp threshold frequency - Braulick, K. W.; Miller, K. C.; Albrecht, J. M.; Tucker, J. M.; Deal, J. E. (British Journal of Sports Medicine, 2013)
Objective: Many clinicians believe that exercise-associated muscle cramps (EAMC) occur because of dehydration. Experimental research supporting this theory is lacking. Mild hypohydration (3% body mass loss) does not alter threshold frequency (TF), a measure of cramp susceptibility, when fatigue and exercise intensity are controlled. No experimental research has examined TF following significant (3-5% body mass loss) or serious hypohydration (>5% body mass loss). Determine if significant or serious hypohydration, with moderate electrolyte losses, decreases TF.